IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILTY - MURTIANINGSIH -; NUR ELIF (Jurnal Akademika, 2017)
This study aims to identify and analyze the impact of the implementation of CorporateSocial Responsibility (CSR) PT. Tirta Investama (Aqua) to the welfare of the community inthe village of Karangjati Pasuruan, with a sample of 205 of 500 families. The type of thisresearch is quantitative descriptive that describes the actual phenomenon. The data used isthe primary data obtained by spreading the questionnaire that has been tested the level ofvalidity with the correlation coefficient (rxy) and the relability with the value of cronbach'salpha more than 0.60. The hypothesis used include the test of influence of education variable(X1), Health (X2), Economy (X3), Environment (X4) on society welfare (Y) by usingmultiple regression analysis at 5% significance level.The test result stated that educational variable of significance value α = 0,023, health α =0,012, Economic α = 0,000, and Environment α = 0,010 have an effect on improvingcommunity prosperity of Karangjati Village with T-value count bigger than T-Table valueand significance level are on α <0.05% indicating that the implementation of CorporateSocial Responsibility in the field of education, health, economics, and environment,conducted by the company has a significant positive effect.Keyword : Corporate Social Responsibility, Educational, health, economic, environment,society welfare